The Effectivity Of Water Tepid Sponge Therapy In Overcoming Nursing Problem Of Hyperthermia In Pediatric With Prolong Fever: A Case Study - Nur, Nadilla Cynthia (Institute of Accounting Research and Novation (IARN), 2023)
One of the most common symptoms that bring patients to health services is fever. Prolong fever is a condition where the child's body is at a body temperature of more than 380C which occurs for approximately 8 days. Improper and slow handling of prolong fever will effect febrile seizures, dehydration, fainting, persistent high fever which causes brain damage. This study aimed to determine the effectiveness of the water tepid sponge intervention in overcoming nursing problem of hyperthermia in pediatric with prolong fever. The research method used is a case study with a nursing process approach starting from assessment to evaluation in children who have prolong fever with hyperthermia nursing problems. One of the interventions and implementations that are carried out based on the results of evidence based practice is water tepid sponge therapy. After 4 days of intervention, the nursing problems in this case study were only partially resolved. Therefore need for further monitoring related to hyperthermia management which includes monitoring body temperature and water tepid sponge therapy.